Effect of Hand Exercise Program on AV-Shunt Maturation in Chronic Kidney Disease Patients: A Literature Review - Ria, Tutur Sahat Dame; Astrid, Maria (GoAcademica Research & Publishing, 2025)
An important aspect in the management of chronic kidney disease is the establishment of adequate vascular access for hemodialysis. Arteriovenous fistula (AV-shunt) is the main and most ideal option for vascular access in the hemodialysis process. This study collected research on the assessment of the effectiveness of hand training programs on arteriovenous shunt (AV-Shunt) maturation in patients with chronic kidney disease (CKD). Searches were conducted on ScienceDirect and Google Scholar. Only experimental studies examining the effects of hand exercises after surgery were reviewed. Data that has been filtered and reviewed by researchers. This study aims to summarize the effects of various hand training programs in the process of AV-Shunt/AVF maturation in CKD patients through a literature review. This study uses the literature review method by analyzing articles from trusted electronic databases such as ScienceDirect and Google Scholar with the keywords maturation AV-Shunt, hand exercises and CKD. The selected articles met the inclusion criteria, namely focusing on hand training interventions analyzed with the PICOT approach. The results of the study show that regular exercise can increase blood diameter and flow, resulting in the patentability of vascular access for the hemodialysis process, which ultimately improves the quality of life. A structured exercise program is an effective intervention in the maturation process of AV-Shunt in CKD patients.